Impact of Stakeholders’ Engagement on Construction Projects: A Case Study of Katsina Central Market - Tor, Mohammed Abba; Gambo, Nasamu (International Journal of Project Management, 2024)
Purpose: There is no doubt that stakeholders’ engagement plays a vital role in ensuring successful implementation and performance of projects generally. This paper examined the effects of stakeholders’ engagement on construction projects in Katsina state. Material and Methods: Using purposive sampling technique, and structured questionnaire administered to 40 sampled professional engineers, business owners, political office holders, community leaders, Findings: The paper found that, the level of stakeholders’ engagement in construction project is low in the study area. Also, the stakeholders’ leadership selection problem is the prime factor that significantly serve as impediments to effective engagement. Improper communication, approach and nature of interaction, political influence and vested interest, Dominance by interest group, Contractual issues and cultural and local values were regarded as the hindrance factors in determining stakeholders’ engagement in construction project. Implications to Theory, Practice and Policy: It is in the wake of these findings this paper recommended that, justice and even distribution of projects, proper communication, community awareness and engagement, avoidance of bureaucratic cumbersome procedures as well as improved nature of interaction would certainly mark a point of departure to making stakeholders’ engagement beneficial and effective for successful implementation of construction projects in the realm. Keywords: Stakeholders, Engagement, Projects, Construction, Katsina